Molecular subtyping of acute myeloid leukemia through ferroptosis signatures predicts prognosis and deciphers the immune microenvironment - Fu, Denggang; Zhang, Biyu; Wu, Shiyong; Feng, Jueping; Jiang, Hua (Frontiers in Cell and Developmental Biology, 2023)
Acute myeloid leukemia (AML) is one of the most aggressive hematological malignancies with a low 5-year survival and high rate of relapse. Developing more efficient therapies are urgent needed for AML. Increasing evidence showed that ferroptosis, an iron-dependent form of programmed cell death, is tightly correlated with cancer initiation and clinical outcome through reshaping tumor microenvironment. However, understanding of AML heterogeneity based on comprehensively profiling ferroptosis signatures is yet to be investigated. Here, 5 independent AML transcriptomic datasets (TCGA-AML, GSE37642, GSE12417, GSE10358, and GSE106291) were obtained from GEO and TCGA databases. Then, we identified two ferroptosis-related molecular subtypes (C1 and C2) with distinct prognosis and tumor immune microenvironment (TIME) by consensus clustering. Patients in C1 subtype were associated with favorable clinical outcome and increased cytotoxic immune cell infiltration including CD8+/central memory T cells, natural killer (NK), non-regulatory CD4+T cells, while decreased suppressive immune subsets such as M2 macrophages, neutrophils, and monocytes. Functional enrichment of differentially expressed genes (DEGs) implied that cell activation involved in immune response, leukocyte cell-cell adhesion and migration, and cytokine production were the main biological processes. Phagosome, antigen processing and presentation, cytokine-cytokine receptor interaction, B cell receptor and chemokine were found as the major pathways. To seize the distinct landscape in C1 vs C2 subtypes, a 5-gene prognostic signature (LSP1, IL1R2, MPO, CRIP1, SLC24A3) was developed using LASSO-Cox stepwise regression analysis and validated in independent AML cohorts. Patients were divided into high- and low-risk groups, and decreased survival were observed in high- vs low-risk group. The TIME between high- and low-risk groups has the similar scenery in C1 vs C2 subtypes. Single cell level analysis verified LSP1 and CRIP1 were up-regulated in AML and exhausted CD8+T cells. Dual targeting on these two markers might present a promising immunotherapeutic for AML. In addition, potential effective chemical drugs for AML were predicted. Thus, we concluded that molecular subtyping using ferroptosis signatures could characterize the TIME and provide implications for monitoring clinical outcome and predicting novel therapy.